Effect of Phase Change Material and Roof Shading on Cooling Load of Residential Unit in Basrah - Naser, Haider Hakeem; Hammadi, Salman Hashim (Basrah Journal for Engineering Sciences, 2022)
In several countries, residential buildings are responsible for high energy consumption. The majority of energy is consumed on air conditioning to ensure maximum indoor comfort. In Iraq, the demand for electricity increases significantly, especially during the summer for cooling purposes. In this paper, two technologies are proposed for buildings to reduce the cooling load. These approaches included the use of phase- changing materials (PCM) in different locations in the walls and roof, in addition to roof shading by galvanized iron. The effects of these proposals were simulated in the latest software tool (designbuilder) and compared with the standard building model. The results were clear when PCM was installed on the outer surface of the wall and roof, which achieved the highest reduction in the cooling load of about 18 %. While the roof shading method using corrugated galvanized iron proved its effectiveness by decreasing the cooling load to 5 % compared to the standard case.